Analysis Of The Causes Of Coconut Production Decline And Its Impact On Farmers' Economy In Durian Payung Village - Zakia, Zul Fahmi; Marifatullah, Awaluddini (Al-Hijrah: Journal of Islamic Economics And Banking, 2023)
Coconut is one of the important agricultural commodities in Indonesia that contributes significantly to the country's economy and the livelihood of farmers. However, in recent years, coconut production in Durian Payung village has experienced a worrying decline. This research aims to analyze the factors that have caused the decrease in coconut production and its impact on the coconut farmers' economy in Durian Payung. The methods used in this study include surveys, interviews, and statistical data analysis related to coconut production from various available sources. The research results show that several factors have led to the decrease in coconut production in Indonesia, including climate change, pest and disease attacks, lack of coconut land maintenance, and the low adoption of modern technology in coconut cultivation. The impact of the declining coconut production on the coconut farmers' economy is significant. Farmers face a drastic decline in income due to the decrease in coconut production, which negatively affects their standard of living and well-being. Additionally, the coconut processing industry and coconut trade are also affected due to limited coconut supply.